(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
Background and Aim. Urinary incontinence (UI) affects up to one in three adults over 50 and is closely associated with stigma, embarrassment, and delayed help‑seeking. Its impact includes psychological distress, social withdrawal, and reduced daily functioning. Although pelvic floor muscle training is an effective conservative treatment, many older adults face barriers related to awareness, guidance, and motivation. Digital health tools may help address these challenges by offering anonymity, structured support, reducing waiting lists and lowering healthcare costs. Evidence from mobile and web‑based UI interventions shows improvements in symptoms and engagement. This study, part of the multinational KOKU Bladder project, explored the needs, expectations, and preferences of a pelvic‑floor digital intervention. Methods. Focus groups were conducted in Spain, the United Kingdom, and Lithuania with adults aged ≥50 (both men and women). Participants completed sociodemographic and ICIQ‑SF questionnaires via REDCap during face-to-face interviews. Qualitative data were analysed using Reflexive Thematic Analysis. Results. Thirty-one potential end users (mean age 62.3 years; 71% women) contributed to the focus groups. UI severity varied widely (ICIQ‑SF 0–16, with a mean of 8.3), and many reported multiple comorbidities. Across countries, Spanish participants emphasised very simple navigation and strong anonymity needs, UK participants showed higher digital confidence and greater openness to optional engagement features, while Lithuanian participants expressed mixed digital skills but a pronounced preference for privacy and clear guidance to ensure exercises were performed correctly. Participants supported reminders and personalised feedback, while views on gamification and virtual communities were mixed. Conclusions. Older adults view a pelvic‑floor digital intervention as acceptable when it is simple, evidence‑based, personalised, and integrated with professional guidance to ensure long-term adherence and effectiveness. Findings directly informed the co‑creation of the KOKU Bladder platform, shaping its educational content, exercise library, and motivational features. Keywords: Urinary incontinence; digital health; eHealth solutions; pelvic floor exercises